Hospitality School Students’ Perception on the Use of Wordwall to Enrich Students’ Work-Ready Vocabulary Mastery - Arsini, Ni Nyoman; Santosa, Made Hery; Marsakawati, Ni Putu Era (Universitas Lancang Kuning, 2022)
This study addressed the gap of research on the innovative learning medium Wordwall for working adult learners by investigating the perceptions of students of Apollonia Hotel School in Denpasar, Indonesia, regarding how well Wordwall helps in increasing their English vocabulary during online learning. The method used by the researcher was qualitative. Data were collected from 10 respondents who had been selected with qualifications of activeness while studying, and always participated during the process. Data obtained from short questionnaire distributed through Google Form, then analysed using a qualitative descriptive model according to Creswell, (2012). From the data analysis, the researcher found that the students had high enthusiasm in learning vocabulary through the Wordwall application. This application provides various types of creative and interactive vocabulary games. The disadvantage is that this application does not provide a place to explain explanations for students' answers, both right and wrong. Students have the opportunity to learn about context and changes to sentences in games. Based on this analysis, it proves that Wordwall is an effective learning media to help increase students' vocabulary as a future career opportunity. In addition, Wordwall is also effectively used during online learning to provide interesting vocabulary questions. From this study, it is suggested for hospitality lecturers to use Wordwall application because it can help students to be more motivated to learn English vocabulary.